Analisis Persepsi Mahasiswa PGSD FKIP Universitas Riau Terhadap Kuliah Daring (Dalam Jaringan) Ditengah Wabah Covid-19 - Prasetiyo, Gusti; Kurniaman, Otang; Noviana , Eddy (Indonesian Research Journal on Education, 2022)
This research is an analytical study to determine the perceptions of PGSD FKIP students at the University of Riau regarding the lecture process carried out online in the midst of the Covid-19 outbreak. Students and lecturers carry out the learning process through technology media. Of course, this lecture system is an alternative way in the midst of the Covid 19 outbreak. Although it is easy to implement the online lecture system, it is necessary to know how students respond to this, why this needs to be done because this is a newthing for students, where lectures which was previously done conventionally or face-to-face was changed to not face-to-face or done online. This research is a research with a quantitative approach, because the data is realized in the form of numbers and analyzed based on statistical analysis. This research is a research with aquantitative approach, because the data is realized in the form of numbers and analyzed based on statistical analysis. This research is also a descriptive research conducted to describe or describe the object of research in the actual situation . The data that has been collected is then described with the help of the calculation of theresults of the questionnaire analysis and documentation in the form of percentages. This study took research subjects, namely PGSD FKIP students from the University of Riau starting from the 2018 batch, 2019 class and 2020 class, totaling 360 students. The data collection technique used in this research is by means of a questionnaire that has been made using google form and distributed online through whatsApp media. Theresults of this study indicate that the perception of PGSD FKIP students at the University of Riau towards online lectures (on the network) amid the Covid-19 outbreak is in the good category.